A Holocene tephra record from the Lofoten Islands, Arctic Norway. - Pilcher, Jon; Bradley, Raymond S.; Francus, Pierre; Anderson, Lesleigh (Boreas, 2005)
A tephrochronology has been established for a peat bog in the Lofoten Islands that provides a dating framework for future lake and bog studies of climate variation in this climatically sensitive area. Twenty‐three tephra layers were identified, all apparently of Icelandic origin. These included the historically dated tephras of AD 1875 (Askja), AD 1362 (Öraefajökull), AD 1158 (Hekla), AD 1104 (Hekla) and the Landnam tephra identified at AD 875 in the GRIP ice core. Other layers, previously radiocarbon dated in Ireland and elsewhere, include the Hekla eruptions of c. 2310 BC and c. 5990 BC. The basal clays below the peat contain tephra of both the Askja eruption of c. 9500 BC (10 000 radiocarbon years BP) and the well‐known Vedde Ash of c. 12 000 BP (10 030 80 BC in GRIP ice core).